Who is on the Rise in Austria : Wage Mobility and Mobility Risk - Thomas Raferzeder; Rudolf Winter-Ebmer (Institute for the Study of Labor (IZA), 2004)
In this paper we investigate earnings mobility in Austria from the angle of individual persons: earnings mobility over time has two aspects: positional changes and the volatility of earnings over time. Whereas the further is a positive outcome, more volatility as such can be seen as negative. We use Austrian data from tax authorities to find out how population characteristics are related to these two concepts of earnings mobility.
Keywords: J31; I32; 330; earnings mobility; earnings volatility; relative income positions; Einkommen; Soziale Mobilität; Volatilität; Einkommensverteilung; Schätzung; Österreich